Spring-back effect on double arrowhead auxetic structures for EV battery compartment protectors - Asep Indra Komara; Indrawanto; Rachman Setiawan; Bagus Budiwantoro; Dedy Ariefijanto (Mechanical Engineering for Society and Industry, 2026)
Cellular structures such as double arrowhead (DAH) have great potential for development as impact-absorbing modules for electric-vehicle battery compartments. The DAH structure is relatively light and absorbs energy well, but the complex manufacturing presents challenges. One potential manufacturing process is sheet metal forming (SMF) technology. In SMF, a common obstacle is spring-back, which affects the assembly process and may reduce the energy-absorption performance of the DAH structure. This article aims to determine the effect of the manufacturing process on the spring-back of the DAH structure on its energy absorption performance. Experimental results showed that all tested conditions produced positive spring-back. Punch velocity had a greater influence than lubrication, where higher punch velocity reduced the spring-back angle, while lubrication showed only a minor effect. The experimental spring-back correction factor (Kθ) ranged from 1.002 to 1.025 depending on the forming conditions. These results indicate that spring-back can be effectively controlled by adjusting punch speed and compensating for tooling angle.